Analysis of The Mute’s Soliloquy Book Written by Pramoedya Ananta Toer About Human Rights Infraction - M. Kevin Khosy (International Journal on Social Science, Economics and Art, 2020)
This research tries to describe about type of human rights infraction which happen to Indonesian Comunist Party’s political captive on Buru Island who written by Pramoedya Ananta Toer on his book called The Mute’s Soliloquy. This captive is captured because their charge of involvement on G30S/PKI tragedy. During their isolation in Buru Island, the political captive treated inhumanly and out of bounds. The Mute’s Soliloquy is chosen because it was a note that written directly by Pramoedya Ananta Toer during his period as political captive on Buru Island. The theory which are used to explain the problems was theory about human rights which is based on the International Covenant on Civil and Political Rights. This covenant has already been ratified by almost member states on United Nation, including Indonesia that ratified this covenant through Law number 12 of 2005. The theory in used to see and analyze type of human rights infraction which happen to political captive on Buru Island. The method of research is qualitative study with descriptive study. The data was collected by library research method. Some type of human rights infraction which happen to political captive on Buru Island is; Right to liberty and security of person, describe about unprocedural arrest of political captive because the obscurity of infringe criminal act and not through a court. Right to hold opinions without interference, describe about limited information that received nor given by political captive. Right to not being held in slavery and hard labour, describe about hard labour which is conducted by political captive, the hard labour is obligation that must be done by political captive on Buru Island. Right to physical integrity, describe about torture that received by political captive, the torture is a sanction or spontaneous treatment by officers. Right to life, describe about death of 310 political captive during detention period on Buru Island with any reasons. After being release from Buru Island, the political captive still get some restriction as civil society.